Use of Social Media at Cardiovascular Congresses: Opportunities for Education and Dissemination - Mihailidou, Anastashia S.; McCall, Debbe; Hiremath, Swapnil; Costello, Briana; Tunuguntla, Anuradha; Mihailidis, Harris (Current Cardiology Reviews, 2021)
Social Media includes different forms of online communication from Twitter, Facebook, Instagram, LinkedIn, podcasts, YouTube etc. and has advanced how information is exchanged. A notable use is engaging on Twitter at medical conferences, both for those attending the conference and the global audience who are not able to attend. It is also increasingly used as an educational tool similar to e-learning. The objective of this paper is to: 1) highlight the impact of using Twitter at cardiovascular congresses as an interactive platform for active learning as compared to passively listening to a presentation; 2) present perspectives from not only clinicians, researchers but also patients on how this information is interpreted; 3) provide recommendations for conference organizers for best practice live tweeting to share the information and knowledge beyond those in attendance; with potential for not only engagement but also educating our global community.
Keywords: medical conference